Compaixão no pensamento do Papa Francisco: a compaixão como chave de leitura da Laudato Si’ - Caraseni, Rita de Cassia Goulart (2017)
This research had as a general objective, to elaborate a study on the compassion category and how it presents itself in the thought of Pope Francisco, especially in the Encyclical Laudato Si'. We had as specific objectives: to characterize the category by relating it to elements identified in the encyclical, investigate and discuss how the category is present in the thought of Francisco and identifying the main meanings of the category in the Encyclical Laudato Si'. The theme of this dissertation arose from the desire to carry out research that treated compassion as a principle to be studied for its relevance in the process of maturing the human being in its relations. As a hypothesis of the research, we consider that the compassion category is expressed in an underlying way throughout the text of the Encyclical, through the use of elements of the category present in the text and also in the interlinkages of the main meanings of the category: anthropological, ecological and theological. The methodological approach used to compose this study was based on bibliographical and documentary research. We looked for authors who representing the state of the art about what was being researched and who presenting a discussion model that was closer to our intention of placing the compassion category in a social and global context, using it as a key to reading. As a result of the research, we note that through compassion, the human being is recognized within life, since this principle is capable of eliminating boundaries, creating bonds of brotherhood and building bridges of accessibility